Combination Phentermine/Topiramate for Obesity Treatment in Primary Care: A Review. Issue 2 (March 2014) - Xiong, Glen L.; Gadde, Kishore M.
Abstract : : The treatment of obesity is often met with a myriad of challenges in the primary care setting. Nevertheless, a modest 5% weight loss is considered clinically significant and may be associated with health benefits. Phentermine/topiramate (Qsymia), available in the United States since September 2012, achieves clinically meaningful weight loss along with improvements in weight–related comorbidities. This combination drug therapy could be an additional tool for primary care providers in their quest for effective management of obesity. Special precautions and close monitoring are indicated when prescribing phentermine/topiramate for women of childbearing potential. Monitoring of heart rate and psychiatric and cognitive side effects is important.